2018
DOI: 10.1016/j.jhazmat.2017.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Activation of persulfate by irradiated laterite for removal of fluoroquinolones in multi-component systems

Abstract: Although several emerging contaminants (e.g. fluoro(quinolones) (FQs)) have been simultaneously detected in environmental systems, there is very limited information on their elimination from contaminated waters in multi-component systems. In this study, removal of three FQs including flumequine (FLU), ciprofloxacin (CIP) and norfloxacin (NOR) were investigated in single and mixture systems, using natural laterite soil and persulfate (PS) under UVA irradiation. Both sorption and oxidation reactions contribute t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…In order to improve removal of pollutants, (NH 4 ) 2 S 2 O 8 was added in two concentrations (0.125 and 0.5 mM) to the reaction mixtures, consisting of emerging pollutant and the catalyst, which showed the highest removal efficiency. As mentioned, in the presence of (NH 4 ) 2 S 2 O 8 it can be expected increased removal of pollutants because of the photochemical activation of (NH 4 ) 2 S 2 O 8 , resulting in sulfate radical anions [44].…”
Section: Removal Efficiencymentioning
confidence: 92%
“…In order to improve removal of pollutants, (NH 4 ) 2 S 2 O 8 was added in two concentrations (0.125 and 0.5 mM) to the reaction mixtures, consisting of emerging pollutant and the catalyst, which showed the highest removal efficiency. As mentioned, in the presence of (NH 4 ) 2 S 2 O 8 it can be expected increased removal of pollutants because of the photochemical activation of (NH 4 ) 2 S 2 O 8 , resulting in sulfate radical anions [44].…”
Section: Removal Efficiencymentioning
confidence: 92%
“…Other AOPs such as electro-Fenton [14], UV photolysis and UV/H2O2 [15] processes were employed to the degradation and the mineralization of ciprofloxacin, and the transformation of some antibiotics shows different structural classes. Recently, Kamagate et al [16] reported that some antibiotics such as flumequine, norfloxacin and ciprofloxacin could be degraded simultaneously by heterogeneous photo-Fenton process using laterite as catalyst. In the case of photocatalysis, most of the researchers have assessed the performance of removal within mono-compound systems [17][18][19].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…TBA and MeOH are used as scavengers for •OH and SO4• - (Zhang et al, 2013). Methanol can remove • OH and SO4• -very quickly, but TBA is relatively inert to SO4• - (Kamagate et al, 2018). Similarly, phenol can also remove •OH, SO4• -and NO3•.…”
Section: The Relative Contribution Of Different Active Speciesmentioning
confidence: 99%